2019
DOI: 10.1111/ijag.13446
|View full text |Cite
|
Sign up to set email alerts
|

Analytical investigation of 14th century stained glass windows from Santa Croce Basilica in Florence

Abstract: The Basilica di Santa Croce (Basilica of the Holy Cross) is the major Franciscan church in Florence (Italy). Among the prominent masterpieces preserved in this church, there are 22 medieval stained glass windows. Between 2000 and 2013, the Opera di Santa Croce started a restoration campaign of six of the most important ones, dated 14th c. In this paper, the archaeometric data collected during the restoration campaign are reported. Two major base glass compositions (potash-lime-silica and soda-lime-silica) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
(16 reference statements)
0
0
0
Order By: Relevance
“…The research on stained-glass windows has been growing in the last years [11][12][13][14][15][16]. However, only 38 published studies were found on grisaille paints characterisation being the oldest from 1984, as shown in Table 1.…”
Section: General Overviewmentioning
confidence: 99%
“…The research on stained-glass windows has been growing in the last years [11][12][13][14][15][16]. However, only 38 published studies were found on grisaille paints characterisation being the oldest from 1984, as shown in Table 1.…”
Section: General Overviewmentioning
confidence: 99%
“…Some medieval stained glass makers recognized that the greenish hue could be overcome by essentially oxidizing the iron ion impurities with the addition of manganese, but this knowledge was not widely communicated and may well have been a tightly held secret. There is also evidence that the glass makers of Santa Croce Basilica in Florence were skilled at fabricating multilayered glasses (7) to create different colors with desired intensities and hues, anticipating by 500 years the multilayered glass windows, lampshades, and other art nouveau pieces created by Tiffany in the latter part of the nineteenth and early part of the twentieth centuries.…”
Section: Stained Glass Windowsmentioning
confidence: 99%
“…6) indicates that these higher levels of titanium, in combination with very low levels of alumina, are not commonly found in Venice (Verità, 2013;Verità andZecchin, 2009a, 2009b). Nevertheless, fourteenth century soda-lime-silica stained glass windows from Santa Croce Basilica (Florence), were tentatively attributed to Venetian production by Verità et al, (2019) , and also show high levels of titanium (on average 0.13%) and low levels of alumina (below 1%) (Fig. 6).…”
Section: Technological Affinitiesmentioning
confidence: 99%
“…The restricted variation of our samples in terms of plant ash components and their similarities to other medieval glasses attributed to Venetian production (Tab.5) can be explained by the mandatory use in Venice, from at least 1255, of Levantine plant ash, "alume catino" as a flux (Zecchin, 1990(Zecchin, :175, 1987(Zecchin, :5, 1997, which was imported, together with raw glass to be remelted, from Syria and Egypt, the ash from the latter considered of poorer quality (Zecchin 1990:173). Use of other types of ash, such as the wood ash used in northern Europe and possibly in other Italian centres such as in Florence (Verità et al, 2019), Pavia (Messiga and Riccardi, 2006) and Orvieto (Kunicki-Goldfinger et al, 2013), was strictly forbidden by the Venetian State (Ashtor and Cevidalli, 1983;Jacoby, 1993;Zecchin, 1990:176). (Verità, 1985) and the low-Al glass samples from the island northern the lagoon of S. Leonardo in Fossamala (11 th -14 th century) (Verità and Toninato, 1990).…”
Section: Technological Affinitiesmentioning
confidence: 99%
See 1 more Smart Citation